Penggunaan Media E-Book dalam Meningkatkan Hasil Belajar (Studi Kasus: Pembelajaran Ekonomi SMA): Penelitian - Triska Aulia Fibrianti; Wahyu Putri Lestari; Yunika Nurfadilla; Zhazha Zahira Ginastuti; Dhiah Fitrayati; Henik Yulia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to improve student learning outcomes through the implementation of a digital-based e-book in Economics subject for Grade X students at SMA Negeri 6 Surabaya. The problem identified is students’ low understanding of the material due to the use of conventional and less interactive learning resources. This research employs a Collaborative Classroom Action Research approach involving teachers and lecturers in planning, implementing, and reflecting on instructional actions. The research subjects were 36 students from class X-1. Data were collected through pre-tests and post-tests, classroom observations, student response questionnaires, and reflective interviews. The results showed an increase in the average score from 63.6 (pre-cycle) to 81.8 (cycle I) and 88.7 (cycle II). N-Gain analysis indicated improvement from moderate (0.50) to high category (0.74). Students also gave positive feedback on the e-book, highlighting its attractive design, accessible content, and integration of formative assessments. The study concludes that an e-book developed based on cognitive learning theory and multimedia learning principles is effective in enhancing conceptual understanding, active engagement, and student autonomy. The novelty of this research lies in the iterative design of the e-book based on student feedback and its collaborative development between teachers and academic practitioners.